Pop-Up Governance: Spatial-Temporal Adaptability of Street-Level Bureaucracy in the Dukcapil on the Street Program in Kuningan Regency - Faiq Nur Rohman; Sri Wulandari (SIGn Journal of Social Science, 2025)
Conventional population administration services frequently encounter constraints due to the temporal limitations of the working-class community. In response to these challenges, the Dukcapil on the Street innovation emerged as a manifestation of temporary, or pop-up, governance, operating tactically within informal public spaces. This study aims to analyze the spatial-temporal adaptability of street-level bureaucracy, explore the deconstruction of public satisfaction, and identify systemic tensions in the field. Utilizing a single-case study approach, primary data were collected through in-depth interviews with four key informants selected via a purposive criterion technique, integrated with unstructured field observations and thematic analysis. The results demonstrated that an operational time compression of 2.5 hours, facilitated by the parallel processing of four work divisions, successfully generated massive productivity without relying on capital-intensive infrastructure. The spatial relocation of service interactions to recreational areas materialized segmented inclusivity for the active workforce and constructed conditional satisfaction through the proactive role of bureaucrats acting as spatial facilitators. Nevertheless, this innovation provoked systemic tensions, manifesting in the absolute rejection of birth certificate amendment requests due to the rigidity of the central physical archives, alongside temporal exclusion resulting from the forceful system closure at exactly 09:00 Western Indonesia Time. In conclusion, this pop-up governance innovation substantiates the high adaptability of bureaucracy, yet it remains fundamentally constrained by the limitations of structural operational capacity. As an operational follow-up, this study recommends adopting securely encrypted mobile digital archival systems and a queue quota pre-registration system.